Profiling morphologic MRI features of motor neuron disease caused by TARDBP mutations - Spinelli, Edoardo Gioele; Ghirelli, Alma; Riva, Nilo; Canu, Elisa; Castelnovo, Veronica; Domi, Teuta; Pozzi, Laura; Carrera, Paola; Silani, Vincenzo; Chiò, Adriano; Filippi, Massimo; Agosta, Federica (Frontiers in Neurology, 2022)
Objective. Mutations in the TARDBP gene are a rare cause of genetic motor neuron disease (MND). Morphologic MRI characteristics of MND patients carrying this mutation have been poorly described. Our objective was to investigate distinctive clinical and MRI features of a relatively large sample of MND patients carrying TARDBP mutations. Methods. Eleven MND patients carrying a TARDBP mutation were enrolled. Eleven patients with sporadic MND (sMND) and no genetic mutations were also selected and individually matched by age, sex, clinical presentation and disease severity, along with 22 healthy controls. Patients underwent clinical and cognitive evaluations, as well as 3D T1-weighted and diffusion tensor (DT) MRI on a 3 Tesla scanner. Grey matter (GM) atrophy was first investigated at a whole-brain level using voxel-based morphometry (VBM). GM volumes and DT MRI metrics of the main white matter (WM) tracts were also obtained. Clinical, cognitive and MRI features were compared between groups. Results. MND with TARDBP mutations was associated with all possible clinical phenotypes, including isolated upper/lower motor neuron involvement, with no predilection for bulbar or limb involvement at presentation. Greater impairment at naming tasks was found in TARDBP mutation carriers compared with sMND. VBM analysis showed significant atrophy of the right lateral parietal cortex in TARDBP patients, compared with controls. A distinctive reduction of GM volumes was found in the left precuneus and right angular gyrus of TARDBP patients compared to controls. WM microstructural damage of the corticospinal tract (CST) and inferior longitudinal fasciculi (ILF) was found in both sMND and TARDBP patients, compared with controls, although decreased fractional anisotropy of the right CST and increased axial diffusivity of the left ILF (p=0.017) was detected only in TARDBP mutation carriers. Conclusions. TARDBP patients showed a distinctive parietal pattern of cortical atrophy and greater damage of motor and extra-motor WM tracts compared with controls, which sMND patients matched for disease severity and clinical presentation were lacking. Our findings suggest that TDP-43 pathology due to TARDBP mutations may cause deeper morphologic alterations in both GM and WM.